Clinical assessment of small bowel capsule endoscopy in pediatric patients - Li, Lin; Zhan, Xue; Li, Jun; Li, Shuyuan; Chen, Yuxia; Yang, Liyan; Wang, Yuting (Frontiers in Medicine, 2024)
Small bowel capsule endoscopy is a first-line examination method for small bowel diseases, which can find small intestinal lumen and mucosal lesions.We retrospectively assessed patients who underwent small bowel capsule endoscopy between September 2020 and May 2023 to examine their clinical and small bowel capsule endoscopic data, aiming to provide insights into the application of this technique in pediatric patients with small intestinal diseases. All instances of capsule retention were successfully resolved through enteroscopy. Of the 1140 children who completed the capsule endoscopy, 97.46% (1111/1140) underwent a comprehensive examination of the entire small intestine without experiencing any discomfort. Capsule endoscopy yielded abnormal findings in 672 cases, with a positive detection rate of 58.95%. Among the positive results, intestinal mucosal inflammatory lesions were the most prevalent, occurring in 292 cases (43.45%), followed by ulcerative or erosive lesions in 236 cases (35.12%), diverticulum in 54 cases (8.04%), and vascular lesions in 30 cases (4.46%). Lymphangiectasis was observed in 16 cases (2.38%). The distribution of positive lesions did not exhibit significant gender-based differences, but there were variations among different age groups. Among all children who completed the small bowel capsule endoscopy, the most frequently reported symptom was abdominal pain (815/1140 cases, 71.49%), followed by 130 cases (11.40%) of bloody stools or melena. Small bowel capsule endoscopy is well-tolerated and safe in children, carrying significant clinical importance for diagnosing abdominal pain and obscure gastrointestinal bleeding in pediatric patients.